Indonesian Nursing Students’ Attributions on Their Improvements in English-Speaking Skills - Santa Maya Pramusita; Dwi Yulianto Nugroho (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
For some people, speaking a foreign language might be exceptionally difficult. Some individuals have a natural aptitude for smooth communication, whereas others face challenges in acquiring this skill. The factors that contribute to individuals speaking a foreign language proficiently came under scrutiny. The objective of this research was to examine the attributions that nursing students had for their improvement in English-speaking skills. Attribution alone pertains to the justifications and rationales individuals offer for their advancement, accomplishment, or even lack thereof in a specific area, such as language acquisition. The study included a total of 38 nursing students from the Faculty of Nursing at Universitas Pelita Harapan in Indonesia. Data collection involved the utilization of open-ended questionnaires and interviews as the primary instruments. The participants were instructed to offer written responses to three items on the questionnaire. Additionally, during the interview phase, the researcher engaged nine participants to elaborate on their written responses from the questionnaire. The data analysis indicated that the primary factors contributing to the improvement of nursing students' English-speaking skills were the importance of doing speaking activities, internal motivation, and amicable learning environment.